ENERGETICS OF STABLE AND METASTABLE LOW-TEMPERATURE IRON OXIDES AND OXYHYDROXIDES - THERMODYNAMIC DATA FOR THE EQUILIBRIA FE-FEO, FE-FE3O4, FEO-FE3O4, FE3O4-FE2O3, CU-CU2O, AND CU2O-CUO FROM EMF MEASUREMENTS - Laberty C.; Navrotsky A. (My University, 1998)
The energetics of a set of synthetic iron oxides and oxyhydroxides were determined by transposed temperature drop calorimetry and high temperature solution calorimetry using sodium molybdate as a solvent at 979 K. The experiments allow the calculation of the enthalpy of formation from the elements of γ-Fe2O3 with tetragonal symmetry (812.7 +/- 2.6 kJ/mol) and with cubic symmetry (-812.3 +/- 2.5 kJ/mol) and β-FeOOH (557.6 +/- 2.4 kJ/mol), values currently unavailable in the literature. Maghemite, γ-Fe2O3, is 15.3 +/- 0.9 kJ/mol less stable in enthalpy than hematite, α-Fe2O3.